Autogenous tooth transplantation: an alternative to replace extracted tooth - David B. Kamadjaja (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: The gold standard treatment to replace missing tooth is dental implants, however, in certain cases, such as in young patients its placement is contraindicated. Autogenous tooth transplantation, which has been widely done in Scandinavian countries for many years, may become a good alternative to overcome this problem. Purpose: This article attempted to provide information about the indication, treatment planning, surgical technique and the successful result of autogenous tooth transplantation. Case: A fifteen year old male patient presented with large caries and periapical disease of his lower left first molar, which was partially erupted and the roots was not fully formed in radiograph. Case management: Autogenous tooth transplantation procedure was performed consisting of extraction of #36, odontectomy of #38 followed by its implantation to socket #36 and fixation of the transplanted tooth to the adjacent teeth. Post operative evaluation was done on regular basis within 18 months period. There was no complaint, the tooth was clinically stable and no evidence of periodontal problem. Serial radiographs showed healing of alveolar bone and periodontal tissue, and the complete root formation was evident by 18 months post operatively. Conclusion: Autogenous tooth transplantation is a potential alternative to replace extracted tooth. Provided that the case be properly planned and operation carefully performed, successful result of this treatment can be achieved.